Awareness of Senior and Specialist Dental Student Toward the Importance of Cost Analysis and Business Practice Management: Cross Sectional Study from a Public University in Indonesia - Anisa Nur Halimah, Aulia Ramadhani (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Dental students not only develop practical skills but also management skills. Dental students must be able to understand how to determine cost analysis, which is a measure of the relationship between costs and output. Objective: to determine the awareness of senior dental student toward the importance of cost analysis and business practice management. Materials and Method: A cross-sectional study was conducted using a questionnaire with closed-ended questions. The study sample included 119 participants in Airlangga Dental College, Surabaya. Statistical analysis was performed by descriptive statistical analysis and chi square tests. Results: One hundred nineteen questioners were returned and analyzed. BDS 95 students while the specialist was 24 students. It was seen that there are 79% of specialist students who have a good level of confidence while in BDS students only 51% have a good level of confidence. BDS students (42%) and specialist students (33%) indicated that their knowledge was sufficient about the costs of practice management or business management. Conclusion: students have confidence in clinical skills but are not quite sure about practice management knowledge. Students are also interested in increasing the range of knowledge about business and practice management.